2011
DOI: 10.1371/journal.pone.0024412
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of HIV-1 Tat on Excitability and Survival of Primary Dorsal Root Ganglion Neurons: Possible Contribution to HIV-1-Associated Pain

Abstract: The vast majority of people living with human immunodeficiency virus type 1 (HIV-1) have pain syndrome, which has a significant impact on their quality of life. The underlying causes of HIV-1-associated pain are not likely attributable to direct viral infection of the nervous system due to the lack of evidence of neuronal infection by HIV-1. However, HIV-1 proteins are possibly involved as they have been implicated in neuronal damage and death. The current study assesses the direct effects of HIV-1 Tat, one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 85 publications
(119 reference statements)
3
32
0
Order By: Relevance
“…To our knowledge, this is the first study that evaluates the effects of Tat on enteric neuronal excitability and the first study to highlight the role of sodium channel expression and kinetics in Tatmediated effects. The direct effects of Tat on neuronal excitability have been previously examined in human fetal brain cells, cultured rat cerebral cortical neurons, and in DRG neurons (Nath et al, 1996;Brailoiu et al, 2008;Chi et al, 2011). In fetal brain cells, Tat induced a depolarization in membrane potentials that were likely due to activation of a nonselective cation channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study that evaluates the effects of Tat on enteric neuronal excitability and the first study to highlight the role of sodium channel expression and kinetics in Tatmediated effects. The direct effects of Tat on neuronal excitability have been previously examined in human fetal brain cells, cultured rat cerebral cortical neurons, and in DRG neurons (Nath et al, 1996;Brailoiu et al, 2008;Chi et al, 2011). In fetal brain cells, Tat induced a depolarization in membrane potentials that were likely due to activation of a nonselective cation channel.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in sodium current density resulted in significant loss of voltage control. This might be due to enhanced expression of Na v 1.8, which appears to be localized on neuronal projections and thus contributes to the inability to adequately control the voltage (Cummins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Tat also appears to have an impact on dopamine (Ferris et al, 2009), norepinephrine (Longordo et al, 2006), glutamate and GABA release (Musante et al, 2010). Moreover, it was recently shown that Tat application increased dorsal root ganglion neuron excitability (Chi et al, 2011). Although these findings suggest that Tat is able to affect neurotransmission, direct evidence of a Tat effect on the molecular process of exocytosis has been missing.…”
Section: Pathological Relevancementioning
confidence: 99%
“…Nef expression in these mice also indirectly contributes to HIV-1-associated neuropathy by enhancing protein expression of other HIV-1 genes and altering cellular maturation in vivo 57 . In vitro exposure to HIV-1 proteins including gp160, gp120, gp41, Tat, Nef, Rev, and Vpr has been reported to initiate neuronal damage [58][59][60][61][62] . Dorsal root ganglion (DRG) neurons have central terminals in the spinal cord dorsal horn and peripheral terminals in skin, muscle and other peripheral tissues.…”
Section: Neuronal Apoptosis Is Associated With Pain In Hiv-1-infectedmentioning
confidence: 99%
“…This increased firing is believed to be critical in the enhanced perception of pain sensation for both inflammatory and neuropathic conditions 64,65 . Our group has recently explored the direct effects of HIV-1 Tat protein on excitability of rat primary DRG neurons 62 . We demonstrated that HIV-1 Tat triggered a rapid and sustained enhancement of the excitability of smalldiameter rat primary DRG neurons, which was accompanied by marked reductions in the rheobase and resting membrane potential (RMP), and an increase in the resistance at threshold (RTh).…”
Section: Neuronal Apoptosis Is Associated With Pain In Hiv-1-infectedmentioning
confidence: 99%